A review of Organopoda Hampson, 1893 (Lepidoptera, Geometridae) from China, with description of three new species - Cui, Le; Xue, Dayong; Jiang, Nan (Zootaxa, 2019)
The Chinese species of the genus Organopoda Hampson, 1893 are reviewed: seven species are reported from China. Three new species, O. acutula sp. nov., O. deltaformis sp. nov. and O. megiste sp. nov. are described. Diagnostic characters of all Chinese species are provided. External features and genitalia are depicted.